Unfavorable Contribution of a Tissue-Engineering Cartilage Graft to Osteochondral Defect Repair in Young Rabbits - Lu, Zhihua; Zhou, Sheng; Vaida, Justin; Gao, Gongming; Stewart, Amanda; Parenti, Joshua; Yan, Lianqi; Pei, Ming (Frontiers in Cell and Developmental Biology, 2020)
A stem cell-based tissue-engineering approach is a promising strategy for treatment of cartilage defects. However, there are conflicting data in the feasibility of using this approach in young recipients. A young rabbit model with an average age of 7.7 months old was used to evaluate the effect of a tissue-engineering approach on the treatment of osteochondral defects. Following in vitro evaluation of proliferation and chondrogenic capacity of infrapatellar fat pad-derived stem cells (IPFSCs) after expansion on either tissue culture plastic (TCP) or decellularized extracellular matrix (dECM), a premature tissue construct engineered from pretreated IPFSCs was used to repair osteochondral defects in young rabbits. We found that dECM expanded IPFSCs exhibited higher proliferation and chondrogenic differentiation compared to TCP expanded cells in both pellet and tissue construct culture systems. Six weeks after creation of bilateral osteochondral defects in the femoral trochlear groove of rabbits, the Empty group (left untreated) had the best cartilage resurfacing with the highest score in Modified O’Driscoll Scale (MODS) than the other groups; however, this score had no significant difference compared to that of 15-week samples, indicating that young rabbits stop growing cartilage once they reach 9 months old. Interestingly, implantation of premature tissue constructs from both dECM and TCP groups exhibited significantly improved cartilage repair at 15 weeks compared to those at six weeks (about 9 months old), indicating that a tissue-engineering approach is able to repair adult cartilage defects. We also found that implanted pre-labeled cells in premature tissue constructs were undetectable in resurfaced cartilage at both time points. This study suggests that young rabbits (less than 9 months old) might respond differently to the classical tissue-engineering approach that is considered as a potential treatment for cartilage defects in adult rabbits.